Microbiome analysis reveals microecological advantages of emerging ditchless rice-crayfish co-culture mode - Huang, Xiaoli; Li, Minghao; Huang, Ya; Yang, Hai; Geng, Yi; Ouyang, Ping; Chen, Defang; Yin, Lizi; Yang, Shiyong; Jiang, Jun; Luo, Wei; He, Zhi (Frontiers in Microbiology, 2022)
Ditchless rice-crayfish co-culture is an emerging model of rice-crayfish farming that circumvents the potential hazards of digging ditches in traditional rice-crayfish farming. However, due to the complex interactions among crayfish, ambient microbiota, and environmental variables, it is necessary to assess the differences in bacterial structure between ditchless and traditional rice-crayfish culture. In this study, the crayfish culture area in the Sichuan basin was selected as the study area, and the bacterial communities of two rice-crayfish culture systems were compared by high-throughput sequencing of 16S rDNA. The results showed that the ditchless system had lower water depth, higher dissolved oxygen, lower total ammonia nitrogen and lower morbidity. There are intuitive differences in the composition of environmental bacterial communities due to environmental changes, even if they are similar in composition at the phylum level. Microbiota in sediments from ditchless systems appear to produce less ammonia nitrogen. The abundance of the pathogens colonising the intestine of ditchless crayfish was lower than ditched one, and the composition was similar to water. Ditch-farmed crayfish appear to be more susceptible to environmental microbes and have a more fragile intestinal structure. Water depth and dissolved oxygen are the main environmental factors that determine the distribution of microbiota. This study is the first to investigate the bacterial ecology of a ditchless rice- crayfish farming system. The results show that the ditchless rice-crayfish culture model has a more superior bacterial system than the traditional rice-crayfish culture.